Profiles, knowledge, skills, abilities, and other characteristics a case of Malaysian government retirees - Yahya, Khulida Kirana; Johari, Johanim; Adnan, Zurina; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (Canadian Center of Science and Education., 2008)
By the year 2020, Malaysia will be an ageing society ignited by the expected increase of senior citizens to 2.71 million.This group consists mainly of the government retirees, who have reached their mandatory retirement age of 56 years old.The objectives of this study are twofold.First, this paper examines the profiles of the Malaysian government retirees and second, to identify the current knowledge, skills, abilities, and other characteristics (KSAOs) they have.To elicit findings,a total of 1609 questionnaires were compiled and analyzed using SPSS.Findings indicate that most of the retirees have acquired numerous KSAOs throughout their years of service, especially in the area that relates to their tasks and responsibilities. However, once they have retired, these retirees are unable to harness their invaluable KSAOs for the country’s development.It is therefore of paramount importance for the government to develop a proper means for the seretirees to utilize their KSAOs.Recommendations emphasize several policy guidelines and activities that can be undertaken by the relevant authorities to help the government retirees transfer their KSAOs appropriately.